2018
DOI: 10.1186/s40942-018-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal dexamethasone implant versus triamcinolone acetonide for macular oedema of central retinal vein occlusion: quantifying efficacy and safety

Abstract: Purpose Among the retinal vascular diseases, burden of retinal vein occlusion is most common immediately after diabetic retinopathy. Intravitreal corticosteroids are gaining popularity in managing macular edema (ME) of RVO. Our study compares efficacy and safety of intravitreal triamcinolone (IVTA) and dexamethasone implant (IVD) over 6 months.MethodsThis comparative, prospective, randomized study on 40 patients of non-ischemic central RVO with significant ME (> 330 μm) of < 3 months duration. Study was done a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
(23 reference statements)
0
8
0
5
Order By: Relevance
“…Although the dependence of the kinetics of drug release from the corneal layers on the layer of major accumulation (e.g., epithelium in case of drug exposure inwards and endothelium/stroma in outward direction) and the transport mechanism (e.g., paracellular or transcellular) must be further investigated, the ability of the cornea to act as a drug reservoir should be considered due to its relevant clinical advantages. If compared to eye drops or injections, drug-eluting implants [ 41 , 42 , 43 ] and therapeutic ophthalmic lenses [ 16 , 44 ] provide sustained ocular delivery and prolong the exposure time of the tissues to the drugs. As a result, drug accumulation in the cornea is favored and its subsequent release could potentially result in a more prolonged therapeutic efficacy of the devices even after their exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dependence of the kinetics of drug release from the corneal layers on the layer of major accumulation (e.g., epithelium in case of drug exposure inwards and endothelium/stroma in outward direction) and the transport mechanism (e.g., paracellular or transcellular) must be further investigated, the ability of the cornea to act as a drug reservoir should be considered due to its relevant clinical advantages. If compared to eye drops or injections, drug-eluting implants [ 41 , 42 , 43 ] and therapeutic ophthalmic lenses [ 16 , 44 ] provide sustained ocular delivery and prolong the exposure time of the tissues to the drugs. As a result, drug accumulation in the cornea is favored and its subsequent release could potentially result in a more prolonged therapeutic efficacy of the devices even after their exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of ME secondary to RVO, IDI was found to be safer than intravitreal TA with regard to IOP. 13 Mylonas et al found a single IDI for postoperative CME can have a similar effect on VA compared with repetitive intravitreal TA. 23 Furthermore, fewer injections minimize exposure to risks such as endophthalmitis, hemorrhage, and retinal tears.…”
Section: Discussionmentioning
confidence: 97%
“…The intravitreal dexamethasone 700 mg implant (IDI) has been used during and after CE. 2,[11][12][13][14][15] Its durability as a sustained-release pellet may provide an advantage over anti-VEGF and TA as a preoperative treatment in eyes at risk for worsening ME due to CE. We performed a retrospective, observational chart review to understand the efficacy and safety of IDI for ME due to RVO, DM, and noninfectious uveitis in patients undergoing CE.…”
Section: Introductionmentioning
confidence: 99%
“…Ancak, hem IVTA hem de deksametazon implantın artmış göz içi basıncı ve erken katarakt oluşumu gibi önemli komplikasyonları vardır. Yapılan çalışmalarda IVTA uygulanan hastalarda deksametazon implant uygulanan hastalara kıyasla bu komplikasyonların daha sık görüldüğü ve daha zor kontrol altına alındığının bildirilmesiyle, benzer etkinliğe sahip endikasyon dahilinde bir ilaç varken, off-label bir ilacın tercih edilmesi yerine deksametazon implant daha ön plana çıkmıştır (15,16). Ancak yine de IVTA'nın bakanlık onayına gerek kalmadan rahatça kullanılabilmesinden ötürü, bu alandaki gerçek kullanım oranını belirleyebilmek güçtür.…”
Section: Bulgularunclassified
“…Ancak, hem IVTA hem de deksametazon implantın artmış göz içi basıncı ve erken katarakt oluşumu gibi önemli komplikasyonları vardır. Yapılan çalışmalarda IVTA uygulanan hastalarda deksametazon implant uygulanan hastalara kıyasla bu komplikasyonların daha sık görüldüğü ve daha zor kontrol altına alındığının bildirilmesiyle, benzer etkinliğe sahip endikasyon dahilinde bir ilaç varken, off-label bir ilacın tercih edilmesi yerine deksametazon implant daha ön plana çıkmıştır (15,16) Ranibizumab için yapılan başvuruların büyük çoğunluğu (%77,8) RVDT tanısı ile olurken, deksametazon implant için ise SRVT ve RVDT için başvuru oranları hemen hemen eşitti (sırasıyla %52,4, %47,6). Başvurularda talepte bulunulan ilacın, istenilen doz şekilleri incelendiğinde, ranibizumab için yapılan başvuruların hepsinde "1 ay arayla 3 doz", deksametazon implant için ise 12 hastada tek doz, 9 hastada ise 2 doz istemi yapılmıştı.…”
Section: Introductionunclassified